Observations on Surgeons' Case Selection, Morbidity, and Mortality Following Board Certification. Issue 3 (March 2016) - Guidry, Christopher A.; Newhook, Timothy E.; Turrentine, Florence E.; Sohn, Min-Woong; Sawyer, Robert G.; Jones, R. Scott
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The purpose of this study is to determine if patient selection varies based on years of surgical practice. Background: The impact of hospital and surgeon volume as a marker of experience has demonstrated an inverse association with surgical outcomes. However, temporal measures of experience often demonstrate no effect. Additionally, a self-reporting survey demonstrated decreasing case complexity over time, suggesting that changes in patient selection may account for some of these observed discrepancies. Methods: General surgery cases at a single tertiary care center reported to the American College of Surgeons National Surgical Quality Improvement Program over a 10-year period were identified. Additionally general surgery cases from the ACS NSQIP 2008 PUF data were used to create risk models for any complications, 30-day mortality, or a composite complication or mortality outcome. These models then estimated risk for our local data. Years of experience after American Board of Surgery certification were calculated for each surgeon for each case. Multivariate linear regression, controlling for surgeon clustering, was used to determine the association between years of surgical experience and preoperative risk of complications and mortality. Results: Eighteen thousand six hundred and eighty eight cases were identified from our institution. Surgeons selected patients of increasing operative risk until 15 years of practice before selecting lower risk patients throughout the rest of their career. After adjusting for risk, no association was observed between years from board certification and mortality. However, there was a trend toward decreasing complication rates with increasing experience. Conclusions: Surgical experience significantly impacts patient selection. Surgeons with over 25 years of experience had lower complication rates. Experience had no impact on mortality.